Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to show that this function $$s:R−>R$$ defined by $$s(x)=(e^x - e^-x)$$ is one to one.

My approach is using the natural $\log{} (\ln{})$ to cancel out the $e$'s:

$e^x - e^{-x} = e^y - e^{-y}$ $$\ln(e^x - e^{-x}) = \ln(e^y - e^{-y}) \\ x + x = y + y \\ 2x = 2y \\ x = y $$

I just wanted to know A. if my algebra is correct and you can do the above operations and B. if it isn't correct, would the next best way to prove its one to one by just plugging in zero for the original functions?


share|cite|improve this question
The algebra is not right. The ln of a sum is not the sum of the ln's. – André Nicolas Mar 14 '13 at 21:18
What sort of tools do you have? I assume you're not supposed to use calculus? – Christopher A. Wong Mar 14 '13 at 21:22
Yes I think it should be done using basic algebra, but if there is a simple way to do prove x = y using calculus I'd be enlightened to see it as well. – Goose Mar 14 '13 at 21:23
A simple calculus-proof would be: Let $f(x) = e^x - e^{-x}$. Then $f'(x) > 0$ for all $x$, so $f$ is strictly increasing and thus $f(x) = f(y)$ implies $x = y$. – TMM Mar 14 '13 at 21:32
@TMM thank you that is pretty simple and makes sense, I'd still like an algebraic one if possible. Gerry Myerson, thanks I just edited my question. – Goose Mar 14 '13 at 21:39
up vote 6 down vote accepted

$$\begin{align} e^x - e^{-x} &= e^y - e^{-y} \\ e^x + e^{-y} &= e^y + e^{-x} \\ e^x(1 + e^{-x-y}) &= e^y(1 + e^{-x-y})\end{align}$$ Since $e^{-x-y} \geq 0$ for all $x,y$ we have $1 + e^{-x-y} \neq 0$, so we can cancel the terms on both sides to get $$e^x = e^y$$ Since $e^x$ is injective, the result follows.

share|cite|improve this answer

Perhaps it is enough to observe that since $e^x$ is strictly increasing $x>y \Rightarrow e^x > e^y$


$e^{-x} < e^{-y}$

$-e^{-x} > -e^{-y}$

$e^x -e^{-x} > e^y -e^{-y}$

share|cite|improve this answer

If $e^x-e^{-x}=w$, then $e^{2x}-we^x-1=0$, a quadratic equation in $e^x$. By the quadratic formula, $e^x=(w\pm\sqrt{w^2+4})/2$. We reject the solution with the minus sign, since it makes $e^x$ negative, which is impossible. So $e^x=(w+\sqrt{w^2+4})/2$, and $x=\log((w+\sqrt{w^2+4})/2)$, a unique solution. So $f(x)=e^x-e^{-x}$ is one to one.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.